Closure of mitral paravalvular defects without performing an arteriovenous loop: a case series of fourteen patients - Kilicgedik, Alev; Gunduz, Sabahattin; Fedakar, Ali; Sunar, Hasan; Izgi, Akin; Türkmen, Muhsin; Ozkan, Mehmet; Kirma, Cevat (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2017)
Introduction: The arteriovenous (AV) loop is recommended when further support is needed during paravalvular leak (PVL) closure. Aim: We report the feasibility and safety of mitral PVL closure without constructing an AV loop, based on a single-centre experience. Material and methods: Fourteen patients with mitral valve replacement (MVR) who had New York Heart Association (NYHA) class III–IV dyspnoea or NYHA class II symptoms with significant haemolytic anaemia caused by severe or moderate-to-severe paravalvular regurgitation and who underwent transcatheter PVL closure (TPVLC) between May 2014 and February 2017 were enrolled. Results : In total, 15 PVL procedures and 19 device deployments were performed. The patients had one (n = 10), three (n = 1) or four (n = 1) devices for closure at the time of the procedure; one patient had two devices from two procedures at different times with different access ways. Nineteen devices (10 (66.6%) via transseptal access; 4 (26.6%), transapical access; and 1 (6.6%), retrograde access) were deployed successfully without making an AV loop. Conclusions : The TPVLC is a less invasive and effective alternative to surgery in symptomatic patients with significant PVLs and high operational risks. The success rates are satisfactory, with improving techniques and devices. Procedural success without using an AV loop can be achieved with reduced costs, fluoroscopic times and complications.